A positive allosteric modulator of mGlu4 receptors restores striatal plasticity in an animal model of l-Dopa-induced dyskinesia. (1st November 2022) - Calabrese, Valeria; Picconi, Barbara; Heck, Nicolas; Campanelli, Federica; Natale, Giuseppina; Marino, Gioia; Sciaccaluga, Miriam; Ghiglieri, Veronica; Tozzi, Alessandro; Anceaume, Estelle; Cuoc, Emeline; Caboche, Jocelyne; et al.
Abstract: By decreasing glutamate transmission, mGlu4 receptor positive allosteric modulators (mGlu4-PAM), in combination with levodopa (l -DOPA) may restore the synergy between glutamatergic and dopaminergic transmissions, thus maximizing the improvement of motor function in Parkinson's disease (PD). This study aimed to clarify the effects of foliglurax, a selective mGlu4-PAM, on the loss of bidirectional synaptic plasticity associated with l -DOPA-induced dyskinesia (LID). Behavioral assessments compared dyskinesia intensity in 6-hydroxydopamine (6-OHDA)-lesioned rats treated with l -DOPA or l -DOPA plus foliglurax. In slices from the same rats, patch-clamp techniques were used to examine electrophysiological differences in glutamatergic synapses, evaluating the EPSCs mediated by NMDA and AMPA receptors in striatal spiny projection neurons. High-frequency stimulation of corticostriatal fibers was used as long-term potentiation (LTP)-inducing protocol. Conversely, 15 min of low-frequency stimulation was applied to depotentiate LTP. The density of dendritic spines was measured in striatal slices in the same experimental conditions. Our results show that, in corticostriatal slices, foliglurax decreased spontaneous glutamatergic transmission in both sham-operated and 6-OHDA lesioned rats. When co-administered with l -DOPA in 6-OHDA-lesioned rats, foliglurax fully restored dendritic spine density in a dose-dependent manner. Moreover, this co-treatment rescued striatal bidirectional plasticity and attenuated the intensity of l -DOPA-induced dyskinesia. This is the first demonstration in an animal model of PD and dyskinesia that a mGlu4 PAM can restore striatal synaptic plasticity. Highlights: MGluR4 PAM foliglurax reduces the excess of glutamatergic transmission in a PD rat model. Foliglurax and l -DOPA co-administration attenuates the intensity of l -DOPA-induced dyskinesia. l -DOPA and modulation of mGluRs rescue dopamine-dependent striatal bidirectional plasticity. MGluR4 PAM combined with l -DOPA restores dendritic spine density in a dose-dependent manner.